Relationship Between Work Motivation and Nurse Performance in the Hemodialysis Unit at RSPAU Dr. Suhardi Hardjolukito Yogyakarta - Wulan Wateriri, Retno; Mahayanti, Agnes; Widianti, Christina Ririn (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Nurses play a pivotal role as the frontline human resources in delivering quality health services. Optimal nursing performance directly influences patient outcomes and organizational success. Motivation is a crucial internal drive that enhances nurse performance, yet its role in specialized settings like hemodialysis units remains underexplored. Objective: This study aimed to examine the relationship between work motivation and nurse performance in the Hemodialysis Room at the Air Force Central Hospital (RSPAU) Dr. Suhardi Hardjolukito Yogyakarta. Methods: A quantitative correlational design with a cross-sectional approach was employed. A total of 24 nurses working in the hemodialysis unit were recruited through total sampling. Data collection utilized validated questionnaires measuring work motivation (intrinsic and extrinsic factors) and performance dimensions. Spearman rank correlation analysis was used to examine the relationship between variables. Results: The majority of nurses (83.3%) demonstrated good work motivation, and 95.8% exhibited good performance. Spearman rank analysis revealed a positive, moderate, and statistically significant relationship between work motivation and nurse performance (r = 0.466, p = 0.022). Conclusion: There is a significant positive relationship between work motivation and nurse performance. Strengthening motivational factors could serve as a strategic lever to enhance nurse performance, particularly in high-demand clinical environments like hemodialysis units.